2014
DOI: 10.1111/sms.12308
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular control, autonomic function, and elite endurance performance in spinal cord injury

Abstract: We aimed to determine the relationship between level of injury, completeness of injury, resting as well as exercise hemodynamics, and endurance performance in athletes with spinal cord injury (SCI). Twenty-three elite male paracycling athletes (C3-T8) were assessed for neurological level/completeness of injury, autonomic completeness of injury, resting cardiovascular function, and time to complete a 17.3-km World Championship time-trial test. A subset were also fitted with heart rate (HR) monitors and their cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…In fact, these values are similar to those reported in the boosted state (Table 1). Similarly, our research on H1 hand cyclists competing at an international level in 2013 found resting SBP to be 112 ± 11 mmHg in the seated position [33]. Of particular note in the study by Blauwet et al is one athlete who competed following recording a pre-race BP of 176/97 mmHg.…”
Section: Boostingmentioning
confidence: 89%
See 4 more Smart Citations
“…In fact, these values are similar to those reported in the boosted state (Table 1). Similarly, our research on H1 hand cyclists competing at an international level in 2013 found resting SBP to be 112 ± 11 mmHg in the seated position [33]. Of particular note in the study by Blauwet et al is one athlete who competed following recording a pre-race BP of 176/97 mmHg.…”
Section: Boostingmentioning
confidence: 89%
“…Recent evidence suggests that the autonomic completeness of injury, assessed by sympathetic skin responses and orthostatic tolerance, can predict aerobic performance in elite athletes with SCI [3,33]. Presently, no studies that compare performance in the boosted and unboosted state have included an assessment of the integrity of spinal autonomic circuits outside of resting and exercise HR and BP measures.…”
Section: Autonomic Nervous System Assessmentmentioning
confidence: 94%
See 3 more Smart Citations